2017
DOI: 10.1167/iovs.17-21475
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Changes After In Vivo Collagen Cross-Linking With Rose Bengal–Green Light and Riboflavin-UVA

Abstract: These results indicate that corneal stiffness increases after CXL, and further increases as a function of time after both RGX and UVX. Also, while biomechanical properties determined after ex vivo CXL are indicative of corneal stiffening, they may not provide entirely accurate information about the responses to CXL in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 34 publications
4
28
0
Order By: Relevance
“…The safety of the treatment was demonstrated through histological analyses showing no thermal damage to retina and iris cells of rabbits after PTB in vivo. 28 Over recent years, more studies on the comparison between collagen crosslinking induced by photo-activated riboflavin and RB on ex vivo and in vivo efficacy, 29 corneal healing response, 30 and collagenase degradation 31 have been performed, showing that treatment with photo-activated RB is more effective than with riboflavin. Based on these results, photo-activated RB to crosslink corneal tissue is considered an attractive therapeutic approach for keratoconus and other disorders and its clinical application in humans should be explored in the near future.…”
Section: Photo-and Sono-activated Rose Bengalmentioning
confidence: 99%
“…The safety of the treatment was demonstrated through histological analyses showing no thermal damage to retina and iris cells of rabbits after PTB in vivo. 28 Over recent years, more studies on the comparison between collagen crosslinking induced by photo-activated riboflavin and RB on ex vivo and in vivo efficacy, 29 corneal healing response, 30 and collagenase degradation 31 have been performed, showing that treatment with photo-activated RB is more effective than with riboflavin. Based on these results, photo-activated RB to crosslink corneal tissue is considered an attractive therapeutic approach for keratoconus and other disorders and its clinical application in humans should be explored in the near future.…”
Section: Photo-and Sono-activated Rose Bengalmentioning
confidence: 99%
“…In vivo , RB 2− ‐photosensitized crosslinking increased cornea stiffness 1.9‐fold after 1 day and 2.8‐fold after 1 month, as measured by tensiometry and by larger factors when estimated from air puff corneal deformation imaging . Significantly, the same level and depth of stromal cell death was found after RB 2− ‐photosensitized crosslinking as for control eyes that were only de‐epithelialized .…”
Section: Clinical Applications Of Photochemical Crosslinkingmentioning
confidence: 70%
“…RF-CXL is toxic to stromal cells and corneal nerves although an in vivo confocal microscopy study confirmed that both the cell density and the nerve density returned to baseline levels after 1 year (92). In animal models, RF-CXL increased corneal stiffness as determined by air puff corneal deformation imaging with finite element modeling and by optical coherence elastography (93,94), consistent with previous studies in ex vivo-treated corneas that indicated~2-fold increase in Young's modulus (95)(96)(97)(98)(99). Responses to RF-CXL in rabbit corneas included downregulation of genes for ECM components and upregulation of glycan and proteoglycan glycosylation (100) as well as stromal cell death throughout the anterior and middle stroma (65).…”
Section: Biomechanical Stiffeningmentioning
confidence: 92%
“…(a) For UVX system, with k'R>>bIgC 1 , bIg'C 1 [O 2 ], as proposed by Kamaev et al [8] Semchishen et al [9] and Lin [4,5] that CXL is predominated by type-I, which does not require oxygen, in contrast to Kling et al [12] proposing type-II oxygen=mediated system. The type-I conversion efficacy, given by C A =1-exp(-S), with S is he time integral of R T , and has a state-state value proportional to the [C 1 /(bI)] 0.5…”
Section: Analysis Of Uvx and Rgxmentioning
confidence: 99%
“…Photochemical kinetics of corneal collagen crosslinking (CXL) has been extensively studied using UVA light and riboflavin (RF) as the photosensitizer [1][2][3][4][5][6]. Much less efforts have been reported using green-light and rose Bengal (RB) as the photosensitizer [7][8][9]. Comparison of animal studies of corneal biomechanical properties after in vivo and ex vivo rose-Bengal-green light (RGX) or riboflavin (UVX) was reported by Bekesi et al CXL anterior part was 100 and 143 to 188 um for RGX and UVX, respectively.…”
Section: Introductionmentioning
confidence: 99%